The Significance of Unique Visual Elements as Identities: Facilitating Effective Wayfinding - Isha Parate; Aparna Parate (Calibrating Urban Livability in the Global South, 2024)
Wayfinding it is a simple cognitive process of the human brain which enables the person to navigate their surroundings through unique visual clues that is the place identity. It is a legible mental map that gives the user an important sense of emotional security. Therefore wayfinding is a dynamic concept that continually adapts to understand and interact with the environment in which the user navigates. Due to the fast pace of development to meet the ever growing demands of the urban population over the globe, be it developed or developing, the cities are growing exponentially resulting in overshowing the local landmarks, hence losing its uniqueness and so affecting the wayfinding process. In a culturally diverse country like India, each location possesses a unique identity, with distinct characteristics emerging every 100 kilometres. The rapid pace of urbanization often blurs the natural and man-made landmarks that serve as crucial visual cues, functioning as an information system for navigation and enriching the unique experience within complex urban environments. This paper places a strong emphasis on the identification, mapping and safeguarding of visual elements as pivotal identities for effective wayfinding in a specific location. Utilizing case studies as valuable tools, the paper examines these unique visual elements; the identities, that act as markers in the wayfinding process. The applied methodology aims to establish a set of guidelines for evaluating both tangible and intangible visual components within a place. In conclusion, the paper underscores the significance of preserving and refurbishing these essential visual cues, as they are indispensable for facilitating effective wayfinding within a given area.